Occurrence of Child and Adolescent Abuse in Caruaru-PE - Ana Flávia GRANVILLE-GARCIA; Valdenice Aparecida de MENEZES; Blancard TORRES FILHO; João Ricardo ARAÚJO; Paula Fernanda Rodrigues SILVA (Association of Support to Oral Health Research (APESB), 2006)
Objective: Verify the occurrence of child and adolescent abuse referred to Caruaru Tutelary Council between 2002 and 2004. Method: To this end, data on the complaints lodged in the period concerned was requested from the Tutelary Council. Results: From a total of 798 cases reported the most common was neglect (49.24%) followed by psychological violence (28.94%). Physical and sexual abuse represented 17.6% and 4.66% of the total of the sample, respectively. As to sex, males represented 55.3% of the cases reported. Conclusion: According to literature, lesions are most frequent on the orofacial area. The awareness of such a piece of information makes a high demand for dental surgeons´ ethical and legal responsibility. Besides reporting suspect child abuse to authorities, there is now a call for creating protective mechanisms for the abused in addition to preventive educational campaigns with focus on the need for denouncing and avoiding all kinds of maltreatment.